C-H functionalization of indoles by 3d transition-metal catalysis - Jagtap, Rahul A.; Punji, Benudhar (Asian Journal of Organic Chemistry, 2019)
Over the past decade, the use of 3d transition metal for the regioselective C-H bond functionalization of indoles has significantly increased. Particularly, advances in manganese, iron, cobalt, nickel and copper catalysis have demonstrated the selective C(2)-H and C(3)-H arylation, alkenylation, alkynylation and alkylation to a greater extent. Similarly, the C-O and C-N bond-forming reactions are manifested via direct C-H bond activation by these earth-abundant metals. The emergence of 3d metals in selective functionalization of the biologically relevant indoles and related heteroarenes would make this protocol more attractive for practical applications. Herein, we provide a brief overview of 3d transition metal-catalyzed (mostly Mn, Fe, Co, Ni and Cu) C-H functionalization of indoles and related heteroarenes.
Keywords: 3d transition metal; C-H functionalization; Indole; indoline

Palladium-catalyzed oxidative annulation of pyrrolylalkyl-1H-azoles: towards the synthesis of polyheterocyclic arenes - Tripathi, Krishna N.; Bansode, Avinash H.; Singh, Ravi P. (Synthesis-Stuttgart, 2020)
A highly efficient and regioselective palladium-catalyzed annulation protocol for a series of linear and terminally substituted 1,2- and 1,3-di(heteroaryl)alkanes to the corresponding polyheterocyclic arenes is reported. Herein, intramolecular oxidative coupling involving double C(sp(2))-H bond functionalization provides a feasible access to biheteroaryl systems annulated to a six-membered ring. The methodology is not restricted to six-membered annulations and was extended to the synthesis of compounds with a seven-membered ring and biheteroaryl core.
Keywords: C-H functionalization; imidazoles; oxidative coupling; Palladium; pyrroles

Nickel-catalyzed C-H bond functionalization of azoles and indoles - Jagtap, Rahul A.; Punji, Benudhar (Chemical Record, 2021)
Direct C-H functionalization of privileged and biologically relevant azoles and indoles represents an important chemical transformation in molecular science. Despite significant progress in the palladium-catalyzed regioselective C-H functionalization of azoles and indoles, the use of abundant and less expensive nickel catalyst is underdeveloped. In the recent past, the nickel-catalyzed regioselective C-H alkylation, arylation, alkenylation and alkynylation of azoles and indoles have been substantially explored, which can be applied to the complex organic molecule synthesis. In this Account, we summarize the developments in nickel-catalyzed regioselective functionalization of azoles and indoles with a considerable focus on the reaction mechanism.
Keywords: azoles; C-C Bond formation; C-H functionalization; indoles; Nickel

Advances in the iron-catalyzed direct functionalizations of heterocycles - Pradhan, Chandini; Punji, Benudhar (Synlett, 2023)
Direct functionalization of heterocycles is an advanced strategy for diversifying privileged and biorelevant heterocycle-containing molecules. Particularly, use of the most abundant transition metal, iron, as a catalyst makes this process highly cost-effective and sustainable. Recently, some progress has been realized towards the direct functionalization of heterocycles under iron catalysis. Herein, we present the developments in the C-H bond functionalizations and related reactions of various heterocycles by abundant iron salts. This Synpacts is categorized into different sections based on heterocycles being functionalized, and each section is discussed based on the type of reaction catalyzed by iron. 1 Introduction 2 Functionalization of Indoles 2.1 Alkylation 2.2 Alkenylation 2.3 Other Reactions 3 Oxindoles and isatins 3.1 C-C Bond Formation 3.2 C-Heteroatom Bond Formation 4 Pyridines and Furans 5 Functionalization of Azoles 6 Summary and Outlook
Keywords: Alkylation; azoles; C-H functionalization; heterocycles; indoles; iron; Mechanism

Enantioselective intramolecular decarboxylative C-H bond func-tionalization of quinazolinones with amino acids by visible light photoredox catalysis - Sonavane, Sameer R.; Mhaske, Santosh B. (Chemistry-An Asian Journal, 2023)
The direct visible light-mediated intramolecular decarboxylative C-H functionalization of Csp(2)-H bond adjacent to the nitrogen of a heteroarene has been achieved by iridium-catalyzed photodecarboxylative radical cyclization. This method offers rapid entry to the synthesis of quinazolinone scaffolds from easily accessible starting materials. The newly developed protocol is mild, operationally simple, oxidant free and general. The utility of this unique Csp(3)-Csp(2) bond forming reaction has been demonstrated in the syntheses of Circumdatin, Sclerotigenine and Benzomalvin A class of quinazolinone natural products and their congeners. The present work represents an interesting example of use of memory of chirality in decarboxylative C-C bond forming enantioselective photoredox reaction.
Keywords: C-H functionalization; memory of chirality; Minisci reaction; photodecarboxylative cyclization; photoredox catalysis; quinazolinone alkaloid; Radical

Late-stage C(sp(2))-H arylation of artemisinic acid and arteannuin B: effect of olefin migration towards synthesis of C-13 arylated artemisinin derivatives - Paul, Sayantan; Ghodake, Balaji M. M.; Bhattacharya, Asish K. K. (Chemistry-An Asian Journal, 2023)
In recent years, C-H bond functionalization has emerged as a pivotal tool for late-stage functionalization of complex natural products for the synthesis of potent biologically active derivatives. Artemisinin and its C-12 functionalized semi-synthetic derivatives are well-known clinically used anti-malarial drugs due to the presence of the essential 1,2,4-trioxane pharmacophore. However, in the wake of parasite developing resistance against artemisinin-based drugs, we conceptualized the synthesis of C-13 functionalized artemisinin derivatives as new antimalarials. In this regard, we envisaged that artemisinic acid could be a suitable precursor for the synthesis of C-13 functionalized artemisinin derivatives. Herein, we report C-13 arylation of artemisinic acid, a sesquiterpene acid and our attempts towards synthesis of C-13 arylated artemisinin derivatives. However, all our efforts resulted in the formation of a novel ring-contracted rearranged product. Additionally, we have extended our developed protocol for C-13 arylation of arteannuin B, a sesquiterpene lactone epoxide considered to be the biogenetic precursor of artemisinic acid. Indeed, the synthesis of C-13 arylated arteannuin B renders our developed protocol to be effective in sesquiterpene lactone as well.
Keywords: Arteannuin B; Artemisinic acid; artemisinin; C-H functionalization; Pd-catalysis

Copper-mediated [3+2] oxidative cyclization of oxime acetate and its utility in the formal synthesis of fentiazac - Jadhao, Nitin L.; Musale, Harish B.; Gajbhiye, Jayant M.; Humne, Vivek T. (Organic and biomolecular chemistry, 2024)
A new protocol for the direct synthesis of 2-aminothiazole has been developed from oxime acetate and readily available sodium thiocyanate using a copper catalyst. The present transformation has good functional group tolerance. Various thiazoles were smoothly synthesized in good to excellent yields. The applicability of the present method has been extended to the formal synthesis of the non-steroidal and anti-inflammatory drug, fentiazac via the Sandmeyer reaction and Suzuki coupling. The direct synthesis of 2-aminothiazole has been developed from oxime acetate using a copper catalyst. The applicability of the present method is used in the formal synthesis of fentiazac.
Keywords: Biological evaluation; C-H functionalization; Vinylazides